Food supply depends on seagrass meadows in the coral triangle - Richard K F Unsworth; Stephanie L Hinder; Owen G Bodger; Leanne C Cullen-Unsworth (Environmental Research Letters, 2014)
The tropical seascape provides food and livelihoods to hundreds of millions of people, but the support of key habitats to this supply remains ill appreciated. For fisheries and conservation management actions to help promote resilient ecosystems, sustainable livelihoods, and food supply, knowledge is required about the habitats that help support fisheries productivity and the consequences of this for food security. This paper provides an interdisciplinary case study from the coral triangle of how seagrass meadows provide support for fisheries and local food security. We apply a triangulated approach that utilizes ecological, fisheries and market data combined with over 250 household interviews. Our research demonstrates that seagrass associated fauna in a coral triangle marine protected area support local food supply contributing at least 50% of the fish based food. This formed between 54% and 99% of daily protein intake in the area. Fishery catch was found to significantly vary with respect to village ( p  < 0.01) with habitat configuration a probable driver. Juvenile fish comprised 26% of the fishery catch and gear type significantly influenced this proportion (<0.05). Limited sustainability of fishery practices (high juvenile catch and a 51% decline in CPUE for the biggest fishery) and poor habitat management mean the security of this food supply has the potential to be undermined in the long-term. Findings of this study have implications for the management and assessment of fisheries throughout the tropical seascape. Our study provides an exemplar for why natural resource management should move beyond biodiversity and consider how conservation and local food security are interlinked processes that are not mutually exclusive. Seagrass meadows are under sustained threat worldwide, this study provides evidence of the need to conserve these not just to protect biodiversity but to protect food security.